A Disciplina Optativa Telessaúde da Universidade Federal do Tocantins como prática educativa inovadora - Filgueira, Michelle de Jesus Pantoja (Universidade Federal de São Paulo, 2017)
This research analyzed the conceptions, expectations and experiences of the teachers, students and medical residents, forefront of the pedagogical proposal of the optional discipline Telehealth from the Medicine´s course of the Federal University of Tocantins, like an innovative strategy of training human resources in health. To reach the proposed objectives was used a methodology qualitative and quantitative through exploratory and descriptive study, using document analysis, case study and an attitudinal perception instrument like Likert, that was applied to teachers, preceptors and students of health courses (medicine, nursing and nutrition), journalism and computer science at the Federal University of Tocantins who attended the optional discipline Telehealth in the period 2011 to 2014. 30 instruments were distributed, with 28 statements each, randomized for five dimensions: the optional discipline telehealth as a stimulator of curriculum innovation program; the optional discipline telehealth as health management tool qualifying (care networks); the optional discipline telehealth as contributory tool in the medical setting in Tocantins; the optional discipline telehealth as contributory tool in the strengthening of Continuing Health Education; the optional discipline telehealth as a stimulus tool inter professionalism. No proposition had been lost in the validation process on dispersed, showing a great validation of content. The reliability was tested by the Spearman – Brown´s formula using the test-retest method with R = 0,97, by the test homogeneity with p-value 0,032 and ANOVA with p-value 0,059, which sets great statistical density for the founded results. All dimensions were in the comfort zone. The data analysis allows the support that innovative aspects have been found in the construction and development from said subject such as: assertiveness in the choice of contents, proper use of teaching and learning active methodologies well as the TIC´s. Some difficulties have been identified as insufficient number of teachers, low participation of preceptors pointing to the need to improve the teaching-service integration and lastly any difficulties in connectivity. This study provides subsidies for advances in the discipline in the light of the principles of pedagogical innovation, meaningful learning and inter professionalism.